Effects of metal mixtures (Cd+Cu+Cr+Pb+Zn) on antioxidant systems and lipid peroxidation in tissues of freshwater fish, Oreochromis niloticus - (:unkn) unknown (Parlar Scientific Publications, 2017)
In the present study, we investigated oxidative stress responses in tissues of Oreochromis niloticus exposed to metal mixtures. Fish were exposed to 0.1 and 1.0 mg/L concentrations of Cd+Cu+Cr+Pb+Zn for 7 and 14 days to determine activities of superoxide dismutase (SOD), catalase (CAT) and glucose-6-phosphate dehydrogenase (G6PD) and levels of reduced glutathione (GSH) and malondialdehyde (MDA) in liver and gills. Beside the elevations of SOD activity and MDA level, general declines were recorded after treatments of metal combinations. Exposure to the heavy metals affected the antioxidant parameters in the tissues, with both CAT and G6PD activities and GSH level in the liver and gill being decreased under metals exposures, especially in their higher concentrations. This study emphasized that the heavy metals can lead to oxidative stress in the O. niloticus and oxidative stress biomarkers may be important in order to evaluate the effects of metal mixtures on aquatic organisms. © by PSP.
Keywords: Antioxidant enzymes; Glutathione; Malondialde-hyde; Metal; Oreochromis niloticus